A Study Redefining the Lowest Point of Mongolia: Монгол орны хамгийн нам цэгийг шинэчлэн тогтоосон судалгаа - Dovchindorj, Ganbold; Bold-Erdene, Galbayar; Avirmed, Erdenedalai; Alimaa, Jijmaa; Munkhsaikhan, Bukhbat (Geographical Issues, 2025)
This study aimed to reassess and redefine the lowest point in Mongolia using modern geodetic and topographic research methods. Previously, the lowest officially recognized point in Mongolia was Khukh Lake in Dornod Province, recorded at an elevation of 560 meters above sea level. However, this study identified a newly discovered low point in Altai Soum, Gobi-Altai Aimag, specifically within the "A" section of the Great Gobi Strictly Protected Area. The precise elevation of this newly identified point was measured at 526.745 meters. To ensure the accuracy of this finding, the study employed advanced surveying techniques, including high-precision Global Navigation Satellite System (GNSS) measurements, innovative geodetic methodologies, and detailed topographic mapping. These methods provided reliable and verifiable data to support the revision of Mongolia’s official geographic records. The identification of this low point holds significant implications for environmental and hydrological studies. The area functions as a natural depression where seasonal water accumulation may occur, making it a valuable site for climate and ecosystem research. Understanding such depressions is crucial for monitoring water balance, sediment deposition, and ecological dynamics in arid and semi-arid regions like Mongolia. Additionally, this discovery has practical applications for updating Mongolia’s geographical databases and can contribute to environmental education and sustainable tourism initiatives. Given the importance of this newly identified lowest point, it is recommended that the site be formally recognized in Mongolia’s official geographic records. Furthermore, long-term monitoring and future research should be conducted to assess its environmental dynamics, potential hydrological significance, and conservation needs. Preserving and utilizing this location for scientific research will provide further insights into the geomorphological and climatic processes shaping Mongolia’s landscape.